Integration of Hadith-Based Fitrah Education and Ki Hajar Dewantara’s Family Education Concept for Children’s Character Building - Yusron Nur Hadi; Niken Ayu Khoirun Nisa`; Abu Bakar Ahmad Baihaqy; Kasan Bisri; Muhammad Kudhori (Jurnal Kawakib, 2026)
The crisis of children’s character in the modern era has become a significant concern due to the weakening role of family education and the influence of digital culture. This study aims to analyze the integration of family education concepts in the perspective of hadith with Ki Hajar Dewantara’s educational thought and its relevance in addressing this issue. The hadith on fitrah provides the theological foundation that every child is born with inherent goodness that must be nurtured by parents. Meanwhile, Ki Hajar Dewantara’s philosophy through the Tri Pusat Pendidikan and Trilogi Pendidikan emphasizes the family as the primary center of character formation through exemplary conduct, motivation, and guidance. This research uses a qualitative literature study by examining hadith, classical Islamic works, and contemporary studies on family education. The findings show that integrating prophetic values with Ki Hajar Dewantara’s philosophy offers a comprehensive framework for strengthening family-based character education in the modern era.